Development of crack on composite detection sensor using magnetic induction concept - N. I. Ismail; W. N. A. Rashid; N. Lokmanulhakim (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A crack detection is very important to control the quality of the composite itself that been widely used in industries. There are quite a numbers of techniques which are used to detect the crack such as visual inspection, radiography, ultrasonic, eddy current magnetic particle, and penetrant testing. In this paper, it focuses on designing and implementing the system to detect a crack on the composite material using magnetic induction concept. At the early stage, the miniature of composite detection sensor using magnetic induction concept is designed using Comsol Multiphysics software to see the current induced from the system. The current value from the sensor is measured based on magnetic induction concept. A complete design of a system then is designed which include the sensor design, the main controller unit design and Bluetooth electronic application. The experiment results show that the magnetic induction concept can be used to detect crack by changing the value of current. When crack occurs the value of current will decrease due to the changes of magnetic induction.